Optimization of the Hull of Fishing Vessels with Fiberglass Base Materials at the Puger Fishing Port (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
The fishing boats used by fishermen on Puger Beach generally still use traditional wooden fishing boats, which were modified from the previous boat design. But over time, the availability of wood decreases. So it is necessary to have alternative basic materials for the manufacture of fishing vessels. An alternative that can replace wood as the basic material for making fishing boats in Puger is fiberglass. Fishing vessels in Puger have varied sizes so it is necessary to analyze the optimum vessel size to operate in Puger. In maintaining ship safety and shipworthiness, a comparison between several parameters of existing fishing vessels is needed. By using the optimization method and then analyzed so that the optimal ship size parameters are obtained. So the optimization results from the ship model in Puger are for a length (L) of 15.57 m, a width (B) of 4.34 m, a ship's height (H) of 1.49 m, and a ship's draft (T) of 0.56 m. From the optimal size of the vessel, then a drawing of the shape of the hull of a fishing vessel made of fiberglass is carried out. The evaluation carried out is the ship's performance such as resistance, stability, and ship seakeeping. So that in determining the shape of the hull which has the characteristics of resistance, stability, and good seakeeping, the ship is in accordance with Puger. So that it can improve and increase the performance of the fishing boats with the aim of the results of this study being to provide recommendations for improving the design of traditional fishing boats in the waters of Puger, Jember Regency